Are Public Sector Tax Practitioners Satisfied with the Services of South Africa Revenue Service? - Oludele Akinloye Akinboade; Mandisa Putuma Mokwena (Central European Public Administration Review, 2012)
The paper discusses the satisfaction with services provided by South Africa Revenue Service (SARS) to public sector tax practitioners to enhance tax compliance. A survey of 375 tax practitioners in eight provinces was made. Tax practitioners appreciate SARS services in paying tax refunds, responding to and handling enquiries, tax practitioners education and the organization of professional training/workshops. Accountants in particular strongly appreciate SARS tax practitioners education. Accountants and older tax practitioners appreciate SARS assistance in completing tax returns. Tax practitioners who work as Financial Managers, Accountants, and those who possess secondary level of education, diploma, degree or have special tax education find tax payer training to be quite useful. Older tax practitioners are more satisfied with SARS office services.